2018
DOI: 10.1016/j.molbiopara.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The pseudo-dimeric tyrosyl-tRNA synthetase of T. brucei aminoacylates cytosolic and mitochondrial tRNATyr and requires both monomeric units for activity

Abstract: Aminoacyl-tRNA synthetases are essential for protein synthesis. The single-copy tyrosyl-tRNA synthetase (Tb-TyrRS) of T. brucei has an unusual structure and forms a pseudo-dimer. It is therefore twice the size than tyrosyl-tRNA synthetases of most other organisms. Here we show by inducible RNAi that Tb-TyrRS is essential for normal growth of procyclic T. brucei. Furthermore we demonstrate that Tb-TyrRS aminoacylates cytosolic as well as mitochondrial tRNA indicating that it is dually localized. Finally we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Finally, it is known that TyrRS classically forms a homodimer and the binding-site for one molecule of tRNA Tyr straddles both subunits (32). In the case of trypanosomatids, our MSA confirms that TyrRS is a double-length enzyme that forms a pseudo-dimer, as previously observed for L. major and T. brucei TyrRSs (33,34). The analysis of the crystallographic structure of L. major TyrRS revealed that the C-terminal monomer is missing some catalytic residues specific of a class I aaRS (KMSKS replaced by ARAVL), and the N-terminal monomer has a 6 residue deletion that structurally affects its anticodon binding domain (33).…”
Section: Identification Of Sequence Peculiarities Of Trypanosomatids Aarsssupporting
confidence: 87%
“…Finally, it is known that TyrRS classically forms a homodimer and the binding-site for one molecule of tRNA Tyr straddles both subunits (32). In the case of trypanosomatids, our MSA confirms that TyrRS is a double-length enzyme that forms a pseudo-dimer, as previously observed for L. major and T. brucei TyrRSs (33,34). The analysis of the crystallographic structure of L. major TyrRS revealed that the C-terminal monomer is missing some catalytic residues specific of a class I aaRS (KMSKS replaced by ARAVL), and the N-terminal monomer has a 6 residue deletion that structurally affects its anticodon binding domain (33).…”
Section: Identification Of Sequence Peculiarities Of Trypanosomatids Aarsssupporting
confidence: 87%
“…Tb TyrRS, like Lm TyrRS, forms a pseudo-dimer and is capable of aminoacylating both mitochondrial as well as cytosolic tRNA Tyr . Furthermore, the deletion of 36 amino acid residues either from the N- or C-termini abolished the Tb TyrRS function, raising the question of what could be the possible role of these amino acid residues in its catalysis . Some of the previously proclaimed antiparasitic plant derivatives such as polyphenolic compounds and alkaloids have been shown to specifically target the active pocket of leishmanial TyrRS with the help of molecular docking analysis. , …”
Section: Research Accomplished On Trypanosomatid Aminoacyl Trna Synth...mentioning
confidence: 99%
“…[13d,36] Thus, we would expect that these 17 aaRSs function in both cytosolic and mitochondrial translation. Indeed, it has been experimentally verified for the cytosolic and mitochondrial GlnRS, GluRS [37] and TyrRS activities, [38] that each are encoded by a single nuclear gene. Typically, most of a given trypanosomal aaRS resides in the cytosol and only a minor fraction is imported.…”
Section: Formation Of Sec-trna Secmentioning
confidence: 99%